The Effect of Toll Gate Type on the Queue of Vehicles in Connecting Roads: A case study of Bawen – Yogyakarta Toll Road - Herna Puji Astutik; Dewanti Dewanti (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Due to the increased population, accessibility from one place to another, and effort to support economic growth, the Indonesian Central Government plans to build 71 kilometers of Yogyakarta-Bawen Toll Road. It is, however, important to state that the technical requirements of a connecting road are an integral part of the toll road construction. Therefore, this research was conducted to determine the sufficient length for the connecting road between the toll gate and existing one to reduce the investment of Toll Road Business Entity and ensure a more extended return period of concession. The data used include the vehicle speed and daily traffic on the road while the maximum length value of vehicle queue occurring in the peak hour period and interval for each type of toll gate was calculated in the modeling simulation. The results showed the satellite gate with 4 lines has 159 meters, tandem with 2 lines has 434 meters, and extending with 3 lines has 513 meters. Since all the gates have less than 2 kilometers of queue length, the stretch of the connecting road in each toll of the plan needs to be analyzed to ensure effective development